Analysis of information security technologies for use in the enterprise infrastructure - A. D. Popov; A. D. Popova (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. The purpose of the study is to analyze modern information security technologies for solving the problems of protecting information in the enterprise infrastructure.Method. The study is based on the methods of system analysis, synthesis, deduction.Result. The analysis was carried out and the features of information protection technology were disclosed for the purpose of possible use in the infrastructure of the enterprise. The analysis of domestic and foreign software for practical use is carried out.Conclusion. The results of the analysis reveal the features of using information protection tools in the enterprise infrastructure in order to counteract modern vectors of attacks on information resources.